EXECUTIVE FUNCTIONING IN CHILDREN WITH NON-VERBAL LEARNING DISABILITY - Kansal, Shweta; Kiran Singh, Thiyam; Malhotra, Nidhi (International Journal of Psychosocial Rehabilitation, 2024)
Nonverbal learning disability (NVLD) is a disorder that is usually seen with significant discrepancies with regards to verbal skills, motor skills, visual spatial skills, and social skills. This becomes a major concern as it leads to learning difficulties. Our objective of the research is to study executive functioning in children with non-verbal learning disabilities. A purposive sample of 45 children, 15 children with non-verbal learning disabilities (NVLD) (as per the Children’s Nonverbal Learning Disabilities Scale), 15 children diagnosed with attention deficit hyperactive disorder (ADHD) according to the DSM-5, and 15 healthy children with a mean age of 9.53 years (SD = 2.13), 10.27 years (SD = 2.40), and 10.67 years (SD = 2.13), were selected from outpatient services of the Department of Psychiatry according to the inclusion and exclusion criteria. For the purpose of the study, the Vanderbilt ADHD Diagnostic Parents’ Rating Scale, Children’s Nonverbal Learning Disabilities (NVLD) Scale, and NIMHANS neuropsychological battery for children, particularly verbal fluency (FAS), verbal N back task, visual N back task, visuo-spatial working memory, Wisconsin card sorting test (WCST), and maze were used. The findings of the present study indicated that there were significant differences among the three groups with respect to error verbal N back 2 (F = 4.24, P<0.05), error visual N back 2 (F = 58.95, P<0.01), and set shifting (F = 13.02, P<0.01), which indicates all three groups have significant differences statistically in terms of executive functioning. From the study, it can be concluded that, as compared to the healthy group, children with NVLD and ADHD performed poorly on the tasks of verbal as well as visual working memory, and between the ADHD and NVLD groups, children with ADHD performed better than children with NVLD. The study also showed that children with ADHD and healthy control performed better than children with NVLD on the task of cognitive set-shifting.